Michael C. Howard y Simione Durutalo, The Political Economy of the South Pacific to 1945. Centre for Southeast Asian Studies, Monograph Series No. 26, Townsville: James Cook University of North Queensland, 1987; 282 pp., un mapa y 28 cuadros estadísticos. - Devalle, Susana B. C. (Estudios de Asia y África, 1988)
-